2021
DOI: 10.1111/imm.13337
|View full text |Cite
|
Sign up to set email alerts
|

CCR8 marks highly suppressive Treg cells within tumours but is dispensable for their accumulation and suppressive function

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 41 publications
2
31
1
Order By: Relevance
“…Interestingly, CCR8 appears to be expressed on T-regs after TCR-mediated activation [ 90 ], and yet, it does not appear to be required for recruitment into melanoma tissues. Indeed, systemic CCR8 ablation had no effect on the infiltration and immunosuppressive function of T-regs in murine melanoma, contrary to previously held assumptions [ 91 ]. For more details, please consult the article written by B Moser for this Special Issue.…”
Section: Chemokine Signals Enabling Immune Evasioncontrasting
confidence: 88%
“…Interestingly, CCR8 appears to be expressed on T-regs after TCR-mediated activation [ 90 ], and yet, it does not appear to be required for recruitment into melanoma tissues. Indeed, systemic CCR8 ablation had no effect on the infiltration and immunosuppressive function of T-regs in murine melanoma, contrary to previously held assumptions [ 91 ]. For more details, please consult the article written by B Moser for this Special Issue.…”
Section: Chemokine Signals Enabling Immune Evasioncontrasting
confidence: 88%
“…Preclinical studies in mice modelling colon (BC38, CT26), melanoma (B16F10), breast (EMT6) and urothelial (MB49) cancer revealed that tumor Treg cells expressed high levels of CCR8 whose targeting in monotherapies with mouse CCR8-specific antibodies resulted in significant inhibition of tumor growth, equivalent to what has been seen with anti-PD-1 blocking antibodies [55][56][57][58][59]. The primary mode of action was reported to involve antibody-dependent cellular cytotoxicity (ADCC) leading to the elimination of CCR8-expressing tumor Treg cells [56,58]. Combination therapies using antibodies specific for both CCR8 and PD-1 led to near complete arrest in tumor progression, indicating that these reagents work in synergy.…”
Section: Ccr8 Marks Activated Intratumoral Treg Cellsmentioning
confidence: 86%
“…As suggested by the recent data from several mouse cancer models [55][56][57][58][59], CCR8 represents a promising target for cancer immunotherapy. Following the lead of mogamulizumab, ADCC-active antibodies to CCR8 could bind to and eliminate tumor-associated Treg cells, notably the most activated and suppressive fraction of Treg cells that selectively express this chemokine receptor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CCR8 is also expressed by Treg cells and its expression is relatively selective for Treg cells and minimal in other immune cells [ 183 , 184 ]. CCR8-expressing Treg cells are also considered to have augmented suppressor activity [ 185 , 223 ]. Indeed, CCR8 has been shown to play a pivotal role in tumor progression by regulating the localization and function of Treg cells in murine cancer models [ 185 ].…”
Section: The Chemokine Superfamily As Therapeutic Targets In Cancer Immunotherapymentioning
confidence: 99%